A study on customers satisfaction towards counter services quality of Social Security Organization (SOCSO) - case study in Kota Bharu, Kelantan / Khairul Farhana Hussain - Hussain, Khairul Farhana (Faculty of Business and Management, 2011)
This study is a research of customers satisfaction towards counter services quality of SOCSO in Kota Bharu. The independent variables consist of timeliness, friendliness and facilities have been identified in order to investigate whether or not these factors have a relationship with dependent variables which is customer satisfaction. This purpose of this research is to measure the level of customer satisfaction on counter services provided by SOCSO. The customers satisfaction may be affected if any modifications have been made on those independent variables due to their linkage to each other and may influence the counter services of SOCSO. The literature review based on varies journal and articles which are relevant to the research are included to verify and sustain that the research is valid. The result of this research are based on the findings and analysis made using the Statistical Package for Social Science Program (SPSS) and illustrates the verification between dependent variables and independent variables. Conclusions and recommendations are comprehended for SOCSO to develop and improve their performance in the upcoming future.